The Relationship Between Students Learning Interests and Numeration Ability in Learning Role Playing: Math Adventure in Class II - Syifaa Kholiqa; Muhammad Makki; Iva Nurmawanti (Yayasan Insan Mulia Bima, 2025)
Education is a way to acquire skills or abilities, one of them is numeracy skills. To achieve this ability, of course the first thing needed is a learning interest for each individual. This study aims to determine the relationship between students learning interests and numeracy skills in role playing: math adventure learning in class II of SDN 12 Cakranegara. This study uses a quantitative approach with the Pearson Product Moment correlation method. The subjects in this study were students of Class II of SDN 12 Cakranegara consisting of 35 students. The data collection technique in this study used a learning interest questionnaire and numeracy ability test questions. The data obtained were reviewed with preconditione tests, specifically normality and linearity tests. Furthermore, assumption test with the Pearson Correlation or commonly called the Product Moment. The result of data assumption showed that the significance value is 0,001, 0,001 < 0,05, it means there is that a significant correlation. Then, seen from the r count value of 0,536 and r table for N= 35 with a significance level 5%, specifically 0,325, 0,536 > 0,325, showed the extent of correlation among the learning interest variable and the numeracy ability variable is belongs to the moderate category. Ho is no accepted and Ha is accepted, it means there is a significant positive or unidirectional correlation between students learning interest to numeracy skills in role playing learning: math adventure in class II of SDN 12 Cakranegara in the 2024/2025 Academic Year.